2012
DOI: 10.1590/s1983-14472012000400026
|View full text |Cite
|
Sign up to set email alerts
|

Produção do conhecimento acerca da formação do enfermeiro na América Latina

Abstract: An integrative literature review with a qualitative approach aimed at understanding the landscape of scientific production in Nursing Education in Latin America, made to understand how it is being conducted the training of future nurses. Data collection was done in the database Latin American and Caribbean Health Sciences, between 2005 and August 2012. The descriptors used were: Higher Education, Curriculum, Teaching, all of them associated with the main descriptor: Nursing Education. We included 82 studies to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
0
3
0
6
Order By: Relevance
“…Na visão dos estudantes de enfermagem a interlocução entre teoria e prática é a maneira mais significativa para o processo de aprendizagem, sendo que a visualização e aplicação prática do que é ministrado em sala de aula favorece ao acadêmico a compreensão do processo de cuidar (19).…”
Section: Discussão E Conclusãounclassified
“…Na visão dos estudantes de enfermagem a interlocução entre teoria e prática é a maneira mais significativa para o processo de aprendizagem, sendo que a visualização e aplicação prática do que é ministrado em sala de aula favorece ao acadêmico a compreensão do processo de cuidar (19).…”
Section: Discussão E Conclusãounclassified
“…A study that analysed the effects of the actions of professors on the education of students concluded that the quality of the professor-student relationship and the existence of personal approaches are considered essential for learning, although they are not isolated from the educational context (12) . In fact, the class is precisely characterised by the relationships between individuals who teach and learn, and their practices seek the intentionalities of the educational projects of the courses and the universities (13) .…”
Section: And It Also Makes a Difference [Knowing The Students] I Knomentioning
confidence: 99%
“…Essas iniciativas são consideradas importantes para dinamizarem o ensino, desenvolverem projetos ativos de aprendizagem e competências dos futuros enfermeiros para a utilização das tecnologias da informação e da comunicação preconizadas pelas diretrizes curriculares nacionais brasileiras (7,8). O emprego de tais recursos tecnológicos possui uma dupla função, a de flexibilizar o ensino de enfermagem por meio de uma proposta pedagógica ativa e a de desenvolver competências com os estudantes no uso de diferentes recursos de informática.…”
Section: Introductionunclassified